2013
DOI: 10.1142/s0218271813500545
|View full text |Cite
|
Sign up to set email alerts
|

The Mass of the Oppenheimer–snyder-Black Hole: Only Finite Mass Quasi-Black Holes

Abstract: Oppenheimer and Snyder (OS) in their paper apparently showed the formation of an event horizon [see Eq. (37) in Phys. Rev. 56 (1939) 455] for a collapsing homogeneous dust ball of mass M as the circumference radius of the outermost surface, r b → r 0 = 2GM/c 2 in a proper time τ 0 ∝ r −1/2 0 in the limit of large Schwarzschild time t → ∞. But Eq. (37) was approximated from Eq. (36) whose essential character is (t ∼ r 0 ln √ y+1where, at the boundary of the star y = r b /r 0 = r b c 2 /2GM . And since the arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…But in the limit ǫ → 0, one has M → 0, so that, the gravitational mass of a neutral point particle M = 0. If so, the density of a dust, a collection of point particles, is zero and which explains why we obtained M = 0 for the Oppenheimer -Snyder black hole [10][11][12].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…But in the limit ǫ → 0, one has M → 0, so that, the gravitational mass of a neutral point particle M = 0. If so, the density of a dust, a collection of point particles, is zero and which explains why we obtained M = 0 for the Oppenheimer -Snyder black hole [10][11][12].…”
Section: Discussionmentioning
confidence: 80%
“…It was indeed shown that Oppenheimer & Snyder black hole tacitly corresponds to M = 0 and which never forms as the comoving proper time τ = ∞ in such a case [10,11]. Even when one would use Kruskal coordinates, it has been shown that, Schwarzschild BHs corresponds to M = 0 [12].…”
Section: Is There Any Exact Solution For Bh Formation?mentioning
confidence: 99%
“…The core of such exhausted star is no longer able to produce sufficient radiation pressure to prevent its outer layer from gravitational collapse. In Newtonian gravitation, the mass of collapsing star ( ) is constant even if it radiates (Mitra & Singh, 2013). Therefore, as radius of star ( ) decreases during the collapse, the ratio of mass to radius increases and leads to the extreme density in the final stable stage of the stellar evolution.…”
Section: Introductionmentioning
confidence: 99%